First-in-human study of neuron regenerative therapy NNI-362 to evaluate the safety, pharmacokinetics, and pharmacodynamics in healthy aged population - Judith Kelleher-Andersson; Esther Yoon; Carol Green; Claire McFarlane; Donya Bagheri; Lynn Parker Thomas; R. Scott Turner (Alzheimer’s Research & Therapy)
Abstract Background A placebo-controlled, double-blind Phase 1a trial examined the safety, tolerability, and pharmacokinetics of NNI-362 as well as the pharmacodynamic outcome of plasma phosphorylated tau181 (p-tau181). Methods Oral NNI-362 and placebo were randomized in healthy, cognitively-unimpaired individuals (ages 50–72) at a 3:1 ratio, with sponsor, principal investigator, and subjects all blinded. Plasma levels of p-tau181 were determined in the placebo and the two highest arms of 120 and 240 mg NNI-362. Plasma biomarker was examined for statistical change from baseline. Results NNI-362 treatment was safe and well tolerated in older individuals. NNI-362, at the two highest multiple doses, significantly reduced plasma p-tau181 levels compared to pretreatment levels (P < 0.0012 to P < 0.0009), while no change occurred in placebo groups. Conclusions These findings suggest in older subjects, oral NNI-362 appeared safe, well tolerated and reduced plasma p-tau181. Phase 2 studies of NNI-362 are warranted for Alzheimer’s disease and age-related degenerative disorders. Trial registry number NCT04074837. First registered: 2019-08-27.